The Principal's Efforts In Building A Solid Work Team At SMA Negeri 3 Kota Jambi - Kholifah, Eling Retno; Suryadi, Suryadi; Muspawi, Mohamad (FKIP Universitas Jambi, 2024)
Education is currently a big challenge that cannot be ignored by any institution, including schools. SMA Negeri 3 Jambi City is one of the schools facing this challenge. In addition to ensuring sustainability, schools must also rethink their leadership approaches to align with national education goals and foster cohesive and unified teams of educators. Addressing these challenges requires thoughtful interventions from all angles. A leadership approach that encourages inclusiveness for all staff members is essential in fostering a strong sense of teamwork among teachers. Therefore, this research aims to explore the role of collaborative leadership in creating a cohesive team that can meet community expectations. Using a qualitative methodology with a focus on literature reviews, this research will examine how the collaborative leadership style of school principals contributes to the development of collaborative teams.